THE EFFECT OF STUDENTSâ€™ READING PROCESS STRATEGIES AND MOTIVATION ON COMPETENCY ACHIEVEMENT IN READING AT STUDENTS FIRST GRADE SEMESTER - Diah Retno Anggraini; Irpa Anggriani Wiharja; Chooi - Heji (Globish: An English-Indonesian Journal for English, Education, and Culture, 2019)
Reading can be characterized as a â€œconceptual processâ€, a tool for thinking and a problem solving process. As a reader, they try to discover what the author means while, at the same time, they build meaning for themselves. They use their own language, their own thoughts, and they own view of the world to interpret what the author has written. These interpretations are limited by what their known. When authors create, they project their language, their thoughts, and their meanings into producing text. Their creations are limited by what they know. Because of obvious differences between the language, thoughts, and authorsâ€™ meaning. Reading can never be an exact process. Because the readerâ€™s own language and thought become involved through interaction with the language and thought of the author, readers can never be certain that they have discovered the meaning the authorsâ€™ write. However, since readers are compelled to understand what they are reading, they interpret actively while reading in order to gain meaning, which is their ultimate goal.The purpose of this research is to know is there any significant effect of studentsâ€™ reading process strategies and studentsâ€™ motivation on reading English text achievement at students first grade semester. This study was quantitative research, 80 students were chosen as a sample with simple random sampling technique. The questionnaires and reading test were distributed to gather the data, and they were analyzed quantitatively.The results of data analysis show that there is an effect of studentsâ€™ reading learning process strategies and studentsâ€™ motivation simultaneously on their reading English text achievement at studentsâ€™ first grade semester. It is proven from the results of statistical calculation that Fobs(132.407) >Ftab(3.33).In conclusion, this study found that reading learning process strategies and motivation used by students positively influenced studentsâ€™ reading English text competency achievement. In line with this conclusion, the writers suggest that the teacher had positive and motivating attitudes.